Alginate and Aloe vera gel-based edible coating for the storage stability enhancement of fresh-cut MD2 pineapple - Yong, Y.Y.; Mohd Adzahan, N.; Abas, F.; Kim, D.O.; Kamarul Zaman, A.A. (Rynnye Lyan Resources, 2022)
Fresh-cut fruits are susceptible to deterioration due to tissue wounding during the preparation process which caused a shorter shelf-life of fresh-cut fruits. This study aimed to compare the storage stability of fresh-cut MD2 pineapples coated with alginate versus fresh-cut MD2 pineapples with Aloe vera gel-based coating. The physicochemical properties, microbiological changes, and quality changes of coated fresh-cut MD2 pineapples were analysed during low-temperature storage (5±1°C) under 85±10% of relative humidity for 16 days. Uncoated pineapples were used as the control and stored under the same storage conditions as the treated pineapples. The Aloe vera-coated pineapples showed a significantly (p < 0.05) lower amount of fluid loss, total plate count, as well as yeast and mould counts, as compared to the uncoated controls. The alginatecoated pineapples were brighter and more yellowish during storage compared to the control, therefore slightly extending the fruit shelf life. Overall, the Aloe vera gel-based edible coating was more effective at retaining the storage stability of fresh-cut MD2 pineapple, as it maintained its microbiological quality for up to 14 days and reduced fluid loss.